Ethical Challenges in the Practice of the Legal Profession in the Digital Era - Siti Handayani Herdiyanti; Hj.Yeti Kurniati; Hj.Hernawati Ras (Formosa Journal of Social Sciences (FJSS), 2023)
Ethical challenges in legal practice in the digital era present significant debate along with the development of information technology. This article explores aspects of data privacy and security, the impact of social media, and the role of artificial intelligence (AI) in legal decision-making. Through a literature review and mixed qualitative and quantitative research methodology, this article discusses the implications of the use of technology, particularly AI, in legal practice and highlights the importance of considering ethical values